The effect of training through the principle of individualization and the principle of play on the dribbling ability of football school players porma aged 10-13 - Yudha Ilhajri Anwar; Ronni Yenes; Emral Emral; Alex Aldha Yudi (Jorpres (Jurnal Olahraga Prestasi), 2023)
This study aims to determine the effect of dribbling training through the principle of individualization on the dribbling ability of football school players (SSB). This type of study is a quasi-experiment. Design This study used a "pretest and posttest one group". The study population was all SSB Porma U players 10-13 years old in Muaro Takung, Sijunjung regency, totaling 28 people, and the number of samples was drawn using saturated sample techniques so that the sample amounted to 28. Instrument in this study with dribbling skill test. Based on the results of data analysis obtained: 1) tcount is 8.127 while ttable is 1.977 then tcalculate ttable which means Ha is accepted and Ho is rejected. So it can be concluded that there is a significant Individualism principle method Dribbling Ability of Football School Players (SSB) Porma Ages 10-13 before and after being given training with. 2) tcount is 1.79 while ttable is 1.71 then tcount ttable which means Ha is accepted and Ho is rejected. So it was concluded that there was a significant difference between the two methods, where the Dribbling Ability of Football School Players (SSB) Porma Ages 10-13 trained with the Individual Method training method (X1) was higher than the playing method (X2). It was concluded that dribbling exercises based on the principle of individualization significantly improved the dribbling ability of school football players (SSB) aged 10-13, compared to the method of playing practice